(untitled) (Journal of Science and Technology, 2016)
In Ghana, the north lags behind the small in industrial development. This is a consequence of direct and indirect national Industrial policy, practice and performance. Recent industrial policy reorientation includes the promotion of small and medium sized industry and entrepreneur development. This _paper gives an appraisal of the entrepreneur potential in the north based on a survey of existing small-scale industrialists. Resources for investment, entrepreneurial qualities and the perspectives to the area were found to be inadequate. hi a rather unfavorable business environment, small-scale industry development seemed to offer high prospects for the industrialization of the rural agrarian. industry - deficiency north in Ghana. The paper therefore advocates a small-scale oriented, entrepreneur-centred industrialization strategy for northern Ghana.